Stability analysis of mathematical model on the effect of modern lifestyles towards the immune system - Alharbi, Sana; Azmin Sham Rambely, (Penerbit Universiti Kebangsaan Malaysia, 2018)
During the last century, lifestyles have changed globally not only in the western countries but also in the developing countries. As a result, the percentages of common fatal diseases, such as obesity, diabetes, cardiovascular disease, and cancer, have dramatically increased, especially in youth. This paper aims to mathematically examine the impact of modern lifestyle on health. Furthermore, we formulate a dynamical model for the impact of a balanced diet, regular exercise and sufficient sleep on the immune system and its processes. We present a stability model of the immune system that includes a cycle of phase-specific vitamins. Ordinary differential equations are used to model the system to describe the functioning of immune cells. The model considers three populations: normal cells, immune cells, and vitamin interventions. The results show that a balanced diet and a healthy lifestyle can boost the immune system and improve its processes to protect a human body from pathogens. In conclusion, a balanced diet and physical activity reduce the percentage of fatal disease risk. Furthermore, it is vital to raise awareness about healthy habits and promote healthy eating, especially for the youth.